The Role of Village-Owned Enterprises as Entrepreneurship Incubators: An Empirical Study in Several Rural Areas - Wening Estiningsih; Pudji Astuty (Greenation Research & Yayasan Global Resarch National, 2025)
This study analyzes the role of Village-Owned Enterprises (BUMDes) as entrepreneurship incubators in rural areas of Indonesia. Using qualitative and quantitative methods, this research examined 15 BUMDes in West Java, Central Java, and East Java from 2022-2024. Data were collected through in-depth interviews with 45 respondents, participatory observation, and document analysis. Results show that BUMDes play a significant role in fostering entrepreneurial spirit among village communities through providing capital access, business training, and business mentoring. Of the 65,941 BUMDes registered nationally, 75.8% are actively operating and have created 142,000 new jobs. BUMDes functioning as entrepreneurship incubators increased village income by an average of 35% and reduced village poverty rates by up to 12%. This research contributes to rural entrepreneurship theory development and provides policy recommendations for optimizing BUMDes function as village economic drivers.